Treinamento pélvico para homens com disfunção erétil após cirurgia de prostatectomia radical: revisão de literatura - Silva, Breno Leonardo Caldeira da (2023)
Introduction: Prostate cancer is one of the most common forms of cancer in men, especially during aging. Radical prostatectomy is an effective treatment option, but complications such as erectile dysfunction (ED) and urinary incontinence (UI) affect quality of life post-surgery. Pelvic floor muscle training (PFMT) is a suggested non-invasive approach to treat these dysfunctions. Objective: to analyze conservative treatment protocols for post-prostatectomy ED through a literature review. Methodology: Searches were carried out on the PEDro and PUBMED platforms with the keywords present in the Health Sciences Descriptors (DeCS): (Prostatectomy) AND (Erectile Dysfunction) AND (Exercise), and in the Medical Subject Headings (MeSH): (Prostatectomy) AND (Erectile Dysfunction) and (Exercise). Randomized and controlled clinical trials were included, in Portuguese, English and Spanish, published in the last 5 years. Reviews, theses and course conclusion works were excluded. Results: After the searches, using the exclusion criteria, three articles were selected, totaling 191 participants. Conclusion: The studies presented heterogeneous methodology, with methodological flaws that did not allow identifying a better form of treatment for post-radical prostatectomy ED. New studies, with larger samples, well-defined selection criteria and well-defined treatment methodology are necessary so that conservative treatment is recommended as an effective tool for treating this dysfunction, which is important for improving the quality of life of affected men